2017
DOI: 10.1111/jam.13548
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological application of yeasts in food science: Starter cultures, probiotics and enzyme production

Abstract: This review is an account of experiences of two research teams (from Italy to Spain); the leading idea is the following: yeasts represent valuable sources in food science and microbiology and are a kind of food factories, because of the potentiality of whole cells or for their produced compounds. This review covers three major areas: the first section addresses the role of yeasts as starter cultures with a special focus on wine. The second section is an update on probiotic yeasts. Finally, the focus of the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 121 publications
0
31
0
4
Order By: Relevance
“…and their metabolites in fermented feed. On the one hand, these probiotics secrete a series of enzymes that effectively degrade anti-nutritional factors to improve the nutrient value of feed materials [18]. On the other hand, probiotics and their functional metabolites, such as organic acids, cell wall polysaccharides, etc., can greatly improve the immune function of animals and inhibit the proliferation of pathogenic microorganisms, thereby maintaining the health of the animals [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…and their metabolites in fermented feed. On the one hand, these probiotics secrete a series of enzymes that effectively degrade anti-nutritional factors to improve the nutrient value of feed materials [18]. On the other hand, probiotics and their functional metabolites, such as organic acids, cell wall polysaccharides, etc., can greatly improve the immune function of animals and inhibit the proliferation of pathogenic microorganisms, thereby maintaining the health of the animals [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…After strain isolation, we characterized yeasts for some enzymatic activities (β-glucosidases, hydrolysis of pectins, sulphite production) and technological properties (ethanol tolerance, resistance to acetic acid). Concerning β-glucosidase, the potential applications of this enzyme include the prevention of sediments in the bottles during storage, as well as the production of volatile compounds [24]. Research on β-glucosidase in yeasts has revealed that most Saccharomyces isolates do not show activity in a natural substrate and that such activity is more frequent in non-Saccharomyces strains [25], from a weak to a strong activity as reported by Fia et al [26] for some strains belonging to Brettanomyces, Metschnikowia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is the traditional species for wine fermentation: it is also an interesting reservoir of probiotic and/or functional strains [6]. It includes the well-known probiotic strain Saccharomyces cerevisiae var.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, S. boulardii possesses good technological performance [3] and can be labeled as a functional starter culture, that is, "a starter culture with an added function, mainly health-oriented or quality-oriented" [11]. The use of yeasts with functional and/or probiotic traits is an increasing trend, and promising strains have been isolated in the past from a wide variety of matrices [6].…”
Section: Introductionmentioning
confidence: 99%